2017
DOI: 10.1016/j.gexplo.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heavy metals in surface soils around the brick kilns in an arid region, Iran

Abstract: There is an increasing demand for the development of brick kilns area in Iran, which emit a considerable amount of pollutants to environment. The present study aimed to investigate the extent of soil contamination by heavy metals around the brick kiln area in Aran-o-Bidgol city. The correlation coefficients, analysis of variance, principal component analysis, cluster analysis, soil contamination indices and interpolation technique were utilized to investigate the soil contamination and pinpoint the possible so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 54 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…As soil pollution arising from brick kiln, the study area have raised attention due to its environmental pollution which is facing serious threats due to elemental pollution originated from the rapid expansion, congestion, and activities from brick kilns [12]. Several studies have reported the concentration of hazardous elements in agricultural soils due to brick kiln in Bangladesh [13][14][15]. The main aim to present research are to address the problem of hazardous elements like Cr, Ni, Cu, As, Cd, and Pb around brick kiln area soils and to find out the ecological risk of such hazardous elements in soils around brick kiln area in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…As soil pollution arising from brick kiln, the study area have raised attention due to its environmental pollution which is facing serious threats due to elemental pollution originated from the rapid expansion, congestion, and activities from brick kilns [12]. Several studies have reported the concentration of hazardous elements in agricultural soils due to brick kiln in Bangladesh [13][14][15]. The main aim to present research are to address the problem of hazardous elements like Cr, Ni, Cu, As, Cd, and Pb around brick kiln area soils and to find out the ecological risk of such hazardous elements in soils around brick kiln area in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies about the manufacture of handmade bricks show that pollutant gases are emitted such as SOx, NOx, CO, CO 2 , particulate matter (PM) or total suspended particulates (TSP)-particles that pass through a size-selective inlet with a 50% cut-off at 1, 2.5 and 10 µm aerodynamic diameter (PM 1 , PM 2.5 and PM 10 , respectively)-metals (Cu, Cr, Pb, Ni, Zn, Cd, Fe, Mn), fluorides and organic compounds (methane, ethane, volatile organic compounds (VOCs)), persistent organic compounds (POPs) and some hazardous air pollutants such as hydrogen chloride (HCl) and hydrogen cyanide (HCN) [64][65][66][67][68][69]. Akinshipe and Kornelius [69] reported that the contribution of brick production to global emissions of black carbon, organic carbon, PM 1 , SO 2 and CO is 5.5%, 2.6%, 1.6%, 2.9% and 1.6%, respectively.…”
Section: Bk Emissionsmentioning
confidence: 99%
“…The calculated coefficient of variation (CV) was 41.23% and 29.21%, indicating moderate variation, which expresses heterogeneous contingency (Zhou et al, 2016), indicating that the sources of heavy metal were not natural, the sources were anthropogenic. Dey and Dey (2017) and Ravankhah et al (2017) reported the heavy metals, i.e., Pb, Cd, Cr and Ni as a major environmental impact factor near brick kilns. The correlation matrix among the soil nutrient factors shows a highly significant positive correlation (p < 0.001), i.e., with soil OM and soil N, P, Na, K, Ca, and Mg but negative correlations with the soil Cd and Pb concentrations in the agricultural sites near the brick kiln cluster (Table 3).…”
Section: Distribution Of CD and Pb In Agricultural Soils Adjacent To mentioning
confidence: 99%
“…The burning of enormous C and N in brick kiln degrades the soils and poses a threat to the environment by provoking atmospheric pollution and climate change (Khan et al, 2007b). In the agricultural soil of the brick kiln area, the concentrations of Cd and Pb were found to be more than the regulatory standards imposed by the US Environmental Protection Agency (Ismail et al, 2012;Ravankhah, Mirzaei, & Masoum, 2017).…”
Section: Introductionmentioning
confidence: 99%